Sensing cellular biochemistry with fluorescent chemical–genetic hybrids. (August 2020) - Gautier, Arnaud; Tebo, Alison G.
Abstract: Fluorescent biosensors are powerful tools for the detection of biochemical events inside cells with high spatiotemporal resolution. Biosensors based on fluorescent proteins often suffer from issues with photostability and brightness. On the other hand, hybrid, chemical–genetic systems present unique opportunities to combine the strengths of synthetic, organic chemistry with biological macromolecules to generate exquisitely tailored semisynthetic sensors.